Analysis of Sales and Cash Receipt Accounting Information Systems to Improve Internal Control at Foto Prima Kediri in 2023 - Marzuki, Ahmad Ma'ruf; Zaman, Badrus; Widiawati, Hestin Sri (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The purpose of this study was to determine the implementation of the sales and cash receipts accounting information system on the internal control system at Foto Prima in 2023. Design/Method/Approach: This research uses descriptive qualitative methods. Research Finding: The results of this study are the implementation of the sales and cash receipts accounting information system at Foto Prima is still not good, it can be seen from the existence of concurrent functions, namely the cash function concurrently with the accounting function, and incomplete accounting documents and records. However, the implementation of the sales and cash receipts accounting information system in internal control at Foto Prima is good as seen from the sequentially numbered printed cash sales invoices, the cash balance from sales is deposited on the same day as the sales transaction and there is a surprise inspection from the business owner of the cash balance. Based on the results of the study, researchers recommend separating the cash function and accounting function to avoid duplication of functions and complete accounting documents or records in order to reduce and prevent manipulation of company data.